2014
DOI: 10.1021/jp503435t
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Hydrate Inhibition of Monoethylene Glycol with Poly(vinylcaprolactam) in Thermodynamically Underinhibited System

Abstract: This study investigates the hydrate inhibition performance of monoethylene glycol (MEG) with poly(vinylcaprolactam) (PVCap) for retarding the hydrate onset as well as preventing the agglomeration of hydrate particles. A high-pressure autoclave was used to determine the hydrate onset time, subcooling temperature, hydrate fraction in the liquid phase, and torque changes during hydrate formation in pure water, 0.2 wt % PVCap solution, and 20 and 30 wt % MEG solutions. In comparison to water with no inhibitors, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 29 publications
0
53
0
Order By: Relevance
“…Raman spectroscopy is a very good instrument method for hydrate qualitative study (including composition [26], structure type identification [57,76]) and quantitative study [19,[80][81][82] (including cage occupancy and hydration number). This information will be applied to the hydrate kinetics process study (including formation [46,51,60,65,[83][84][85], dissociation [33,36,64,86], gas replacement [50,60,87,88], and inhibitors [47,89]), structure changes [8,11,31,34,35,41,45,49,90], hydrate distribution [26,38,43], and structural characterization [91][92][93].…”
Section: Application Of Raman Spectroscopy To Clathrate Hydrate Studymentioning
confidence: 99%
“…Raman spectroscopy is a very good instrument method for hydrate qualitative study (including composition [26], structure type identification [57,76]) and quantitative study [19,[80][81][82] (including cage occupancy and hydration number). This information will be applied to the hydrate kinetics process study (including formation [46,51,60,65,[83][84][85], dissociation [33,36,64,86], gas replacement [50,60,87,88], and inhibitors [47,89]), structure changes [8,11,31,34,35,41,45,49,90], hydrate distribution [26,38,43], and structural characterization [91][92][93].…”
Section: Application Of Raman Spectroscopy To Clathrate Hydrate Studymentioning
confidence: 99%
“…Daraboina et al (Daraboina et al, 2013) reported that PEO and NaCl could enhance the nucleation inhibition strength of Luvicap. Kim et al (Kim et al, 2014) reported that mixing of monoethylene glycol with PVCap in underinhibited conditions would induce the synergistic hydrate inhibition by delaying the hydrate onset time as well as preventing the agglomeration and deposition of hydrate particles. As the earliest KHI polymer, PVP is the representative product of the first generation KHIs, which has provided theoretic and practical basis for design and development of the subsequent generation of KHIs.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of gas hydrates is a serious problem in hydrocarbon exploitation, transportation, and processing, for example, plug the flow lines and choke valves. Hence, it is of great importance to prevent gas hydrate formation to avoid these operational problems. , Monoethylene glycol (MEG) is a solvent capable of blending with free water, changing the thermodynamic conditions and avoiding the undesirable formation of gas hydrates. MEG presents advantages in relation to other inhibitors (for example, methanol): relative low viscosity that gives better outflow, easy recovery based on its low volatility in relation to water, low solubility in liquid hydrocarbons, and low toxicity. …”
Section: Introductionmentioning
confidence: 99%